Listening Effort During Sentence Processing Is Increased for Non-native Listeners: A Pupillometry Study - Borghini, Giulia; Hazan, Valerie (Frontiers in Neuroscience, 2018)
Current evidence demonstrates that even though some non-native listeners can achieve native-like performance for speech perception tasks in quiet, the presence of a background noise is much more detrimental to speech intelligibility for non-native compared to native listeners. Even when performance is equated across groups, it is likely that greater listening effort is required for non-native listeners. Importantly, the added listening effort might result in increased fatigue and a reduced ability to successfully perform multiple tasks simultaneously. Task-evoked pupil responses have been demonstrated to be a reliable measure of cognitive effort and can be useful in clarifying those aspects. In this study we compared the pupil response for 23 native English speakers and 27 Italian speakers of English as a second language. Speech intelligibility was tested for sentences presented in quiet and in background noise at two performance levels that were matched across groups. Signal-to-noise levels corresponding to these sentence intelligibility levels were pre-determined using an adaptive intelligibility task. Pupil response was significantly greater in non-native compared to native participants across both intelligibility levels. Therefore, for a given intelligibility level, a greater listening effort is required when listening in a second language in order to understand speech in noise. Results also confirmed that pupil response is sensitive to speech intelligibility during language comprehension, in line with previous research. However, contrary to our predictions, pupil response was not differentially modulated by intelligibility levels for native and non-native listeners. The present study corroborates that pupillometry can be deemed as a valid measure to be used in speech perception investigation, because it is sensitive to differences both across participants, such as listener type, and across conditions, such as variations in the level of speech intelligibility. Importantly, pupillometry offers us the possibility to uncover differences in listening effort even when those do not emerge in the performance level of individuals.